Mesh nebulizers enabling transnasal pulmonary delivery of medical aerosols to infants and toddlers: Roles, challenges, and opportunities - Ari, Arzu; Rubin, Bruce K.; Fink, James B. (Frontiers in Drug Delivery, 2022)
The development of mesh nebulizer technology has expanded the ability to deliver medical aerosols to infants and small children via nasal cannula and prongs. Mesh nebulizers do not need compressed gas to generate aerosols with a smaller and lighter profile facilitating placement in delivery circuits, unlike jet and ultrasonic nebulizers. Prior to this century, aerosol delivery with the nasal interface to 1 – 4 kg infants or surrogate animal models was limited to low single-digit deposition. In vitro and animal studies with enabling mesh technology increases inhaled dose by upwards of 14% with nasal continuous positive airway pressure. Recently, investigations of transnasal aerosol delivery to the lung have expanded to nasal cannula interface with both high and low flow oxygen administration, nasal continuous positive airway pressure therapy, and noninvasive ventilation in treating respiratory distress, respiratory insufficiency, and acute respiratory failure of infants and toddlers. We will first examine the progression of testing transpulmonary delivery of medical aerosols from in vitro models to in vivo animal and human studies. Then, we will explain current and developing applications in clinical practice to view future directions and opportunities.